2009
DOI: 10.1590/s0103-64402009000300010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of psychopathologies on craniomandibular disorders

Abstract: Psychopathologies play a role in the etiology and maintenance of craniomandibular disorders (CMD). In this study, the craniomandibular index was applied to valuate signs and symptoms of CMD in 60 dentate patients, who were assigned to 2 groups: symptomatic (n=35) and asymptomatic (n=25). An interview on psychopathologies was carried out with the aim to detect the presence of some mood disorders, such as depression, dysthymic and bipolar I disorders. Among these disturbances, depression was the most significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
7
0
2
Order By: Relevance
“…In 70% of studies individuals were assessed based on RDC/TMD as a diagnostic criterion. Other diagnostic criteria were Graded Chronic Pain Scale (Park et al, 2010; Velly et al, 2011), Guideline of diagnosis of TMD by the American Academy of Orofacial Pain (Kindler et al, 2012; Boggero et al, 2016), Diagnostic Criteria for FM (Nilsen et al, 2008; Pfau et al, 2009; Velly et al, 2010; Alfvén, 2012; García-Moya et al, 2015), International Classification of Headache Disorders II (Mongini et al, 2007; de Tommaso et al, 2009), International Headache Society (Glaros et al, 2007), Diagnostic and Statistical Manual of Mental Disorders-IV (Mongini et al, 2007; Vidaković et al, 2016), Craniomandibular Index (Penna et al, 2009), and Craniomandibular Index/RDC (Velly et al, 2011). In three studies only healthy subjects were included and RDC/TMD were treated as excluding criteria (Slade et al, 2007; Komiyama et al, 2008; Manfredini et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 70% of studies individuals were assessed based on RDC/TMD as a diagnostic criterion. Other diagnostic criteria were Graded Chronic Pain Scale (Park et al, 2010; Velly et al, 2011), Guideline of diagnosis of TMD by the American Academy of Orofacial Pain (Kindler et al, 2012; Boggero et al, 2016), Diagnostic Criteria for FM (Nilsen et al, 2008; Pfau et al, 2009; Velly et al, 2010; Alfvén, 2012; García-Moya et al, 2015), International Classification of Headache Disorders II (Mongini et al, 2007; de Tommaso et al, 2009), International Headache Society (Glaros et al, 2007), Diagnostic and Statistical Manual of Mental Disorders-IV (Mongini et al, 2007; Vidaković et al, 2016), Craniomandibular Index (Penna et al, 2009), and Craniomandibular Index/RDC (Velly et al, 2011). In three studies only healthy subjects were included and RDC/TMD were treated as excluding criteria (Slade et al, 2007; Komiyama et al, 2008; Manfredini et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty research teams have investigated the relationship between MFP and depression. Twenty-four of these (Mongini et al, 2007; Slade et al, 2007; Ivkovic et al, 2008; de Tommaso et al, 2009; Galli et al, 2009; Manfredini et al, 2009; Penna et al, 2009; Shibuya et al, 2009; Giannakopoulos et al, 2010; Park et al, 2010; Velly et al, 2010, 2011; Buenaver et al, 2012; Guarda-Nardini et al, 2012; Kim et al, 2012; Kindler et al, 2012; Shedden Mora et al, 2012; Yachida et al, 2012; Pelkonen et al, 2013; Cioffi et al, 2014; Klasser et al, 2014; Mladenović et al, 2014; Boggero et al, 2016; Vidaković et al, 2016) have found a significant correlation between these issues and six studies have not (Nifosì et al, 2007; Reissmann et al, 2008; Pfau et al, 2009; Manfredini et al, 2011; Pizolato et al, 2013; Calixtre et al, 2014). The quality of evidence in the first group was moderate due to the limited generalizability of the reported results, while in the second group the score was low.…”
Section: Resultsmentioning
confidence: 99%
“…An increased prevalence of TMD among the elderly who reported these symptoms was observed. Studies report that tinnitus and dizziness are common in elderly patients (6,7,(22)(23)(24) , as well as in patients with TMD (25)(26)(27) . Depression was a stronger predictor associated with prevalence of TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Depression was a stronger predictor associated with prevalence of TMD. Psychological factors are indicated as etiological for TMD in many studies; however, little is known about the relationship between TMD and neurophysiological etiology of depression (27)(28)(29) . The presence of clicks in the TMJ during opening and closing of the mouth was observed with the aid of a stethoscope placed near the external ear.…”
Section: Discussionmentioning
confidence: 99%
“…Жалобы неадекватны болевым стимулам, не исчезают после применения анестетиков, НПВП, не соответствуют областям иннервации краниальных нервов или известным зонам иррадиации. Могут наблюдаться вегетативные расстройства в виде нарушения трофики и потоотделения; симптоматика обычно возникает на фоне нарушений сна [41,44]. У 7% пациентов при обострении хронической ЛБ имеется сочетание повышенного уровня стресса и тревоги [45].…”
Section: психогенная больunclassified